PENGARUH STRES KERJA, BURNOUT DAN MOTIVASI KERJA TERHADAP KINERJA PERAWAT RSD MANGUSADA KABUPATEN BADUNG - Bagiada, I Putu Surya; Netra, I Gusti Salit Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.05.TAHUN 2019, 2019)
Performance is the result of person’s work in certain period by carrying out some tasks. This study aims to determine the effect of job stress, burnout and work motivation on performance at Mangusada Hospital. The population is 186 nurses with 127 people as samples, using propotionate stratified random sampling.. Multiple linear regression was used. The study found that job stress and burnout had a negative and significant effect on nurse performance. Work motivation has positive and significant effect on nurse performance. Efforts to improve performance are expected to need to pay attention to the comfort when working with colleagues and nurses must get the appropriate work schedule, then need to pay attention to the ability of nurses to handle the number of patients and make the work atmosphere not monotonous. Providing clear targets, fostering a sense of responsibility towards work and giving appreciation to nurses will motivate nurses to work.